Diabetes as a Negative Risk Factor for Abdominal Aortic Aneurysm – Does the Disease Aetiology or the Treatment Provide the Mechanism of Protection? - Torsney, Evelyn; Pirianov, Grisha; Cockerill, Gillian W. (Current Vascular Pharmacology, 2013)
There is strong epidemiological evidence that patients with diabetes have a lower incidence of abdominal aortic aneurysm. The precise mechanism of this negative association is unknown. Whilst a number of studies have supported the hypothesis that protection is a function of diabetes-mediated changes in the vascular extracellular matrix biology, there is also support for the idea that the treatment regimens used in diabetes may afford protection against AAA. In particular the pleiotropic drug family, the thiazolidinediones have been examined as candidates to ameliorate aneurysm formation. Both the thiazolidinediones, and the structurally related family, fibrates, have been shown to have anti-inflammatory and antioxidative effects, in addition to ability to modulatate glucose and lipid homeostasis. In this brief review we present the current data exploring the use of thiazolidinediones in experimental aneurysm development. Despite the fact that both thiazolidinediones Rosiglitazone and Pioglitazone are no longer prescribed in Europe and the US, they have provided important insights into the mechanism of action, and the application of other pleiotropic drugs in the treatment of AAA. One such pleiotropic drug is high-density lipoproteins (HDLs), which have been shown to have a broad spectrum of effects, including activation of PPARs, which may favour their use as a new drug target for protection against AAA development.
Keywords: peroxisome proliferator-activator receptors